Impact of Different e-Cigarette Generation and Models on Cognitive Performances, Craving and Gesture: A Randomized Cross-Over Trial (CogEcig) - Caponnetto, Pasquale; Maglia, Marilena; Cannella, Maria Concetta; Inguscio, Lucio; Buonocore, Mariachiara; Scoglio, Claudio; Polosa, Riccardo; Vinci, Valeria (Frontiers in Psychology, 2017)
Abstract Introduction Most E-cigarettes are designed to look like traditional cigarettes and simulate the visual, sensory, and behavioural aspects of smoking traditional cigarettes. This research aimed to explore whether different e-cigarette models and smokers’ usual classic cigarettes can impact on cognitive performances, craving gesture. Methods The study is randomised cross-over trial designed to compare cognitive performances, craving, and gesture in subjects who used first generation electronic cigarettes, second generation electronic cigarettes with their usual cigarettes. (Trial registration: ClinicalTrials.gov number NCT01735487). Results Cognitive performance was not affected by “group condition”. Within-group repeated measures analyses showed a significant time effect, indicating a increase of participants’ current craving measure in group “usual classic cigarettes (group C)”, “second generation electronic cigarette 24 mg nicotine (group H), second generation electronic cigarette, model Ego C loaded with liquid nicotine 9 mg (group E) . Measures of gesture not differ over the course of the experiment for all the products under investigation Conclusion All cognitive measures attention, executive function and working memory are not influenced by the different e-cigarette and “sex” showing that in general electronics cigarettes could become a strong support also from a cognitive point of view for those who decide to quit smoking. It seems that not only craving and other smoke withdrawal symptoms but also cognitive performance is not only linked to the presence of nicotine; this suggests that the reasons behind the dependence and the related difficulty to quit smoking needs to be looked into also other factors like the gesture